WILL THE COVID-19 PANDEMIC CHANGE ANYTHING? – A VIEW FROM THE ANGLE OF EXPERTS IN MICROBIOLOGY - Delic, Snezana (HEALTH CARE, 2020)
The COVID-19 pandemic has shaken the majority of health systems around the world, pointing outthat it is necessary to invest in the modern equipment for molecular diagnostics, as well as to providean adequate space within microbiological laboratories for this form of diagnostics, according to thestandards that are required for such procedures. It is also necessary to increase the number of specialistswithin the field of medical microbiology, especially in those laboratories where the lack of experts is atan alarming level. Investing in the diagnostic branches of medicine (and microbiology, as well) providesthe optimal health protection: fast and correct diagnosis, the application of the adequate antimicrobialtherapy as soon as possible, resulting in greater chances for curing. Furthermore, this leads to fewerhospital days and fewer deathly outcomes, while for infirmary patients this means a faster diagnosticprocedure and a decrease in the number of specialist examinations, which are sometimes unnecessary.During the Covid-19 pandemic, The Section of Microbiologists of the Serbian Medical Society as well asthe Institute for Microbiology and Immunology of the Faculty of Medicine of Belgrade University, havemade themselves available to the Ministry of Health of The Republic of Serbia for the identification ofpotential laboratory capacities and for conducting necessary experts training, for doctors specialistsand for laboratory technicians, as well. Although new technologies develop fast and the laboratory workbecomes automated, in theory and in practice as well, an educated expert in medical microbiology stillpresents the main pillar that stands up for a precise, modern, quick and high-quality diagnosis ofinfective pathogens, especially those with pandemic potential.
Keywords: COVID-19, pandemic, microbiological diagnostics, infectious diseases